PENGARUH MOTIVASI PENGEMBANGAN KARIR DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. PERTAMINA PATRA NIAGA REGIONAL KALIMANTAN - Bani Anhar (STIE Madani Balikpapan, 2025)
This study aims to determine the effect of motivation, career development and work discipline on employee performance at PT. Pertamina Patra Niaga Regional Kalimantan. This research is quantitative. The population in this study were employees of PT. Pertamina Patra Niaga Regional Kalimantan. The sampling technique used in this study was saturated sampling, meaning that all employees of PT. Pertamina Patra Niaga Regional, totaling 50 employees, were the samples in this study. The data used in this study are primary data obtained by directly distributing questionnaires to all employees. The data analysis technique used in this study is the multiple linear regression method assisted by the SPSS 25 program. The results of this study indicate that partially the motivation variable has a negative and insignificant effect on employee performance, the career development variable partially does not have a negative and insignificant effect on employee performance and work discipline partially has a positive and significant effect on employee performance. Keywords: motivation, career development, work discipline, employee performance